Functional electrospun nanofibres for heat dissipation applications - Sharif, Mohd Luqman Hakim (2021)
With the rapid growth in electronic power density, effective heat dissipation has been the primary issue to be addressed in the continuous development of industrial electronics, which aims to minimize size while increasing performance. This has resulted in experts working hard to create innovative and effective ways to deal with the problem of heat dissipation at high temperatures, in order to improve the heat transfer rate between hot surfaces and the environment by increasing the heat transfer coefficients or expanding the heat transfer area. Nanofiber was discovered to be one of the potential alternative materials that could serve the purpose in heat dissipation application due to its large Surface Area to Volume Ratio (SAVR). Most of the time, the nanofiber is fabricated by means of bicomponent extrusion, phase separation, template synthesis, drawing, melt blowing, centrifugal spinning, and electrospinning. As for this study, electrospinning is utilized by using Polyacrylonitrile-Dimethylformamide (PAN-DMF) solution to produce PAN nanofibers. Two samples were prepared with different tip-to-collector distances; Sample I = 10cm and Sample II = 20cm, to establish the minimum and maximum size of PAN nanofibers that could be produced under the limitation imposed by the currently available electrospinning machine in the Advanced Materials Characterization Laboratory (AMCHAL) in UTeM, Melaka. Both of the samples were characterized on their respective morphology and fiber diameter to be used as a reference in Computational Fluid Dynamics (CFD) simulation in ANSYS Fluent. The simulations of the fibers were conducted as steady-state thermal analysis with the Turbulence Model of Realizable k-epsilon with enhanced wall treatment. The morphology of the fiber resembles a somewhat smooth cylindrical solid with a continuous, and randomly oriented pattern while the diameter of the fiber produced was 1.24μm and 717nm, respectively. From the simulation, the total Heat Flux dissipated with regard to SAVR constant volume were 104.35992 × 103 W for Nanofiber Model and 104.35989 W for Microfiber Model. Due to the value of SAVR in nanofiber was discovered to be inversely related to the diameter of the nanofiber, nanofiber with smaller diameter will dissipate heat better than nanofiber with greater diameter, particularly when heat dissipation is required in very tiny areas